The The railway museum as memory institutions and tourism attractions: Case study in area a of the Ombilin Coal Mining Heritage of Sawahlunto - Hendrawan, Muhammad Rosyihan; Mat Isa, Azman; Samsudin, Ahmad Zam Hariro (Record and Library Journal, 2025)
Background of the study: Museums serve as memory institutions and also function as tourist attractions. The Railway Museum at OCMHS preserves Indonesia’s industrial heritage, yet its effectiveness in balancing heritage conservation and visitor engagement remains understudied. This study assesses its role, strengths, and challenges, particularly in promotion, community involvement, and innovative programming. Purpose: The research aims to evaluate how effectively the museum fulfils its dual role as a memory institution and a tourism attraction. Method: This study utilizes a qualitative case study approach, gathering data through interviews, observations, and document analysis, with a focus on museum staff, management bodies, visitors, and the curator. Findings: This study indicates that the museum effectively showcases its historical artefacts, providing a meaningful cultural experience while attracting visitors. The museum features well-curated exhibitions of colonial-era railway artefacts that help understand local industrial heritage. However, there are challenges related to promotional activities, community engagement, and innovative programming aimed at enhancing visitor experiences. Conclusion: The study concludes that the Railway Museum plays a significant role in heritage preservation and tourism. However, improvements in community-based tourism initiatives and marketing strategies are essential to fully realize its potential as a cultural and tourism asset in the region.